Athanasius and the Holy Spirit: the development of his early pneumatology - Hill, Kevin Douglas (Emerging scholars, 2016)
"Athanasius of Alexandria wrote over seven dozen works, the majority of which contain at least one reference to the Holy Spirit. Yet, previous studies have primarily concentrated on Athanasius's Letters to Serapion on the Holy Spirit (ca. 359-361), leaving a lacuna in our knowledge of Athanasius's prior pneumatology. By exploring the period from Athanasius's election as bishop (328) to the completion of the third Oration against the Arians (ca. 345), this book seeks to help fill this gap. The first part argues that by the mid-330s, Athanasius had begun to establish core pneumatological perspectives that he would maintain for the rest of his career. Part 2 examines Athanasius's three Orations, giving particular attention to Orations 1-2. To Athanasius, the Holy Spirit is eternal, uncreated, united to the Son, worthy of worship, and essential for salvation. These points laid the foundation for what was to come in Serapion. Without the pneumatological perspectives that he established in the 330s and 340s, Athanasius would not have been prepared to take the next steps of confessing the Holy Spirit's divine nature and role in creating the world."--Page 4 of cover